Kinetic Model For Growth And Influence Of Ph On The Growth Of Halochlorella Rubescens In A Fabricated Photobioreactor - Izatul Anis Muhammad Jais, Nur (Pusat Pengajian Teknologi Industri, 2020)
For years, Chlorella sp, have been proven to be one of the candidates in producing abundant amounts of algal biomass. In this study, the fabrication of a new reactor was done and performance of Halochlorella rubescens, microalgae under genus Chlorella sp. in producing high cell mass was studied. Microalgae cell activation profile in three different cultivation volumes (500 mL, 1 L and 5 L) at normal cultivation mode and effect of pH towards the algae growth kinetic in a fabricated 15-L photobioreactor was investigated. 500 mL culture recorded highest biomass concentration and biomass productivity of 2.493 g/L and 0.183 g DW L-1 d -1. Dilution of cell lines and inoculum age are found to have notable effects towards microalgae growth. Highest biomass concentration and biomass productivity,1.689 g/L and 0.1043 g DW L-1 d -1 was recorded when the microalgae cultivated in pH 10.5 culture and high alkalinity medium showed remarkable effects towards the microalgae productivity. Two growth models, Logistic and Gompertz tested in this study to determine the growth model for microalgae in fabricated reactor. R2 values obtained for pH 8.5, 10.5 and 13.5 from both Logistic and Gompertz are 0.9634, 0.9482, 0.7225 and 0.9626, 0.9474, 0.7249 respectively. This shows that this microalgae best-fitted with Logistic model and growth kinetics of Halochlorella rubescens can be determined by using this model